Zunaj Gutenbergovega vesolja - Kodrič-Dačić, Eva (Knjižnica, 2006)
Technological development has changed the media and formats for recording information, as well as the methods for their collection, preservation, reproduction and use. After six and a half centuries since the invention of printing press, electronic publications on Internet represent a revolutionary break-through in communication and data transmission. The new format has changed the publication to the extent that the library science should re-define the topic of its research, and re-consider the methods and procedures for its treatment. Consequently, the library science should refer to the underlying terminological and typological research, and re-define the subject of bibliographic processing and determine the elements for the subject's identification. The new technological platform of electronic publications opens a range of possibilities, which make the significance and value of the established methods of knowledge management very relative, and thus also the basis of the library science and its "raisson d'ętre". No cultural value is attached to electronic publications due to their specific characteristics, as it has been attached to a book in our civilization. Therefore, collection and long-term preservation of this material is not problematic only from the technological but also from the sociological aspect. By dealing with electronic media, library theory and practice finally step from the area of the known laws of the Gutenberg universe into the new space, where the new working rules will have to be established.
Keywords: elektronske publikacije; bibliografska obdelava; digitalizacija; digitization; tipologija; zbiranje; arhiviranje